2023
DOI: 10.1007/s40993-022-00419-5
|View full text |Cite
|
Sign up to set email alerts
|

The scheme of monogenic generators I: representability

Abstract: This is the first in a series of two papers that study monogenicity of number rings from a moduli-theoretic perspective. Given an extension of algebras B/A, when is B generated by a single element θ ∈ B over A? In this paper, we show there is a scheme M B/A parameterizing the choice of a generator θ ∈ B, a "moduli space" of generators. This scheme relates naturally to Hilbert schemes and configuration spaces. We give explicit equations and ample examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…• M. E. Charkani and A. Deajim [26] (see also A. Deajim and L. El Fadil [28]) x p − m over number fields • M. Sahmoudi and M. E. Charkani [148] considered relative pure cyclic extensions • A. Soullami, M. Sahmoudi and O. Boughaleb [150] x 3 n + ax 3 s − b over number fields • O. Boughaleb, A. Soullami and M. Sahmoudi [23] x p n + ax p s − b over number fields • H. Smith [152] relative radical extensions • S. K. Khanduja and B. Jhorar [138] give equivalent versions of Dedekind criterion in general rings • S. Arpin, S. Bozlee, L. Herr and H. Smith [5], [6] study monogenity of number rings from a modul-theoretic perspective • R. Sekigawa [149] constructs an infinite number of cyclic relative extensions of prime degree that are relative monogenic…”
Section: The Relative Casementioning
confidence: 99%
See 1 more Smart Citation
“…• M. E. Charkani and A. Deajim [26] (see also A. Deajim and L. El Fadil [28]) x p − m over number fields • M. Sahmoudi and M. E. Charkani [148] considered relative pure cyclic extensions • A. Soullami, M. Sahmoudi and O. Boughaleb [150] x 3 n + ax 3 s − b over number fields • O. Boughaleb, A. Soullami and M. Sahmoudi [23] x p n + ax p s − b over number fields • H. Smith [152] relative radical extensions • S. K. Khanduja and B. Jhorar [138] give equivalent versions of Dedekind criterion in general rings • S. Arpin, S. Bozlee, L. Herr and H. Smith [5], [6] study monogenity of number rings from a modul-theoretic perspective • R. Sekigawa [149] constructs an infinite number of cyclic relative extensions of prime degree that are relative monogenic…”
Section: The Relative Casementioning
confidence: 99%
“…• Z. Fran ȗsić and B. Jadrijević [63] calculated generators of relative power integral bases in a family of quartic extensions of imaginary quadratic fields • I. Gaál [65] showed that index form equations in composites of a totally real cubic field and a complex quadratic field can be reduced to absolute Thue equations • I. Gaál [68] showed that the index form equations in composites of a totally real field and a complex quadratic field can be reduced to the absolute index form equations of the totally real field • I. Gaál [66] considered generators of power integral bases in fields generated by monogenic trinomials of type x 6 + 3x 3 + 3a • I. Gaál [67] considered generators of power integral bases in fields generated by monogenic binomial compositions of type (x 3 − b) 2 + 1 • I. Gaál [70] gave an efficient method to determine all generators of power integral bases of pure sextic fields • I. Gaál and L. Remete [78] considered monogenity in octic fields of type K = Q( 4√ a + bi) • I. Gaál [69] determined "small" solutions of the index form equation in K = Q( 6 √ m), for −5000 < m < 0 such that x 6 − m is monogenic (1521 fields) Experience: 6 √ m is the only generator of power integral bases • I. Gaál [71] determined "small" solutions of index form equations in K = Q( 8 √ m), −5000 < m < 0 such that x 8 − m is monogenic (2024 fields) Experience: 8 √ m is the only generator of power integral bases, except for m = −1 • I. Gaál [72] extended [54] on monogenity properties of trinomials of type x 4 + ax 2 + b • I. Gaál [73] calculated generators of power integral bases in families of number fields generated by a root of monogenic quartic polynomials considered in [88] In [72], [73] the method described in Section 4.4 was used, in [63], [78], [71], its relative analogue, see [76], [64].…”
Section: Explicit Calculations Algorithmsmentioning
confidence: 99%
“…Mostly, Dedekind's criterion is used. [106,107] studied monogenity of number rings from a modul-theoretic perspective; • R. Sekigawa [108] constructed an infinite number of cyclic relative extensions of prime degree that are relative monogenic.…”
mentioning
confidence: 99%